Teknoteologi dan Teologi Post-Sistemik: Model 3D dalam Formasi Iman di Era Digital - Eko Wahyu Suryaningsih; Yesaya Bangun Ekoliesanto; Hyuman Noguchi (Sekolah Tinggi Theologia Nazarene Indonesia, 2026)
The development of digital culture has rapidly shaped the characteristics of the digital generation (Generation Z and Alpha). Consequently, it calls for a theological model that is more adaptive, dialogical, and contextual in responding to the dynamics of the digital age. This study aims to formulate technotheology as a post-systematic theological framework that bridges Christian faith with the realities of digital culture through a 3D model (Discern, Design, Deploy). This research employs a qualitative method with a conceptual-reflective approach based on literature studies in digital theology, contextual theology, and critiques of modern systematic theology. The findings indicate that technotheology functions as a reflective framework that does not replace systematic theology but rather extends it through a more communicative and participatory post-systematic approach. The proposed 3D model enables the ethical and biblical discernment of digital values (Discern), the creative and contextual formation of faith (Design), and the implementation of faith witness in digital spaces (Deploy). The novelty of this study lies in the formulation of technotheology as a conceptual framework within post-systematic theology through the 3D model.